Neuman Systems Model in perioperative nursing care for adolescents with juvenile idiopathic scoliosis - Márcia Pestana-Santos; Margarida da Silva Reis Santos; Ivone Evangelista Cabral; Paula Cristina Sousa; Maria de Lurdes Lopes de Freitas Lomba (SciELO, 2021)
ABSTRACT Objective: To implement the nursing process, based on the Neuman Systems Model and the International Classification of Nursing Practice terminology, in the care of an adolescent who underwent corrective surgery for juvenile idiopathic scoliosis. Method: This is a qualitative study of the type of single case, with triangulation of data collection techniques (formal clinical interview, notes in a field diary and medical record information), developed with a 17-year-old adolescent and indication for corrective surgery. The empirical materials generated with the interviews carried out at admission and at discharge, observation and medical record information were treated with categorical content analysis. Results: The categories of personal condition, anxiety, selfconcept, meaningful people, facilitating health resources, school, free time and leisure were recurrent. Diagnoses were defined with a focus on Anxiety, Knowledge on pain management (control) and Willingness (or readiness) to learn, associating them with the respective nursing interventions. Conclusion: The Model contributed to assess and recognize surgery stressors for the adolescent and to theoretically base the nursing process. The classification allowed systematizing nursing care records, elements of clinical practice, unifying vocabulary and codes.